2015
DOI: 10.1097/pas.0000000000000457
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of “Poorly Formed Glands” Gleason Pattern 4 Prostatic Adenocarcinoma on Needle Biopsy

Abstract: Accurate recognition of Gleason pattern (GP) 4 prostate carcinoma (PCa) on needle biopsy is critical for patient management and prognostication. "Poorly formed glands" are the most common GP4 subpattern. We studied the diagnostic reproducibility and the quantitative threshold of grading GP4 "poorly formed glands" and the criteria to distinguish them from tangentially sectioned GP3 glands. Seventeen urologic pathologists were first queried for the definition of "poorly formed glands" using cases representing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Substantial additional variability arises from applying discrete categorizations to glandular differentiation that lies on a continuous spectrum, such as the Gleason pattern 3/4 transition between small glands and poorly defined acinar structures or the Gleason pattern 4/5 transition between fused glands and nests or cords. 12,44,45 Our data show that for regions where pathologists are discordant in Gleason pattern categorization, where the underlying histology is likely closer to the cusp between patterns, the DLS reflects this ambiguity in its prediction scores (Fig. 4b) and demonstrates the potential to assign finer-grained Gleason patterns (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Substantial additional variability arises from applying discrete categorizations to glandular differentiation that lies on a continuous spectrum, such as the Gleason pattern 3/4 transition between small glands and poorly defined acinar structures or the Gleason pattern 4/5 transition between fused glands and nests or cords. 12,44,45 Our data show that for regions where pathologists are discordant in Gleason pattern categorization, where the underlying histology is likely closer to the cusp between patterns, the DLS reflects this ambiguity in its prediction scores (Fig. 4b) and demonstrates the potential to assign finer-grained Gleason patterns (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Unfortunately, many studies have shown that the evaluation afforded by current histopathology techniques is often neither accurate nor reproducible, with high levels of inter-observer variability between pathologists regarding critical elements such as carcinoma grade and molecular phenotype [ 6 , 51 , 52 ]. For example, a recent study examined the inter-observer agreement within a panel of genitourinary pathologists in distinguishing between the “poorly formed gland” variant of Gleason pattern 4 prostate carcinoma versus tangentially sectioned Gleason pattern 3 glands (i.e., “well-formed glands”), and reported relatively poor inter-observer concordance ( κ = 0.34) [ 53 ]. The distinction between Gleason pattern 3 and 4 carcinoma can result in dramatically different treatment recommendations: namely, active surveillance (Gleason pattern 3) versus radical prostatectomy (Gleason pattern 4), with its associated iatrogenic risks (incontinence, impotence, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…The three-dimensional continuity of these patterns is reflected by the substantial inter-observer variability in daily pathology practice. Distinguishing, on one hand, tangentially sectioned Gleason pattern 3 glands from poorly formed and fused Gleason pattern 4 glands, and, on the other hand, poorly formed Gleason pattern 4 glands from Gleason pattern 5 cords on hematoxylin and eosin slides is the principal area of difficulty [12, 14, 27, 28]. Secondly, there are serpentine compact irregular epithelial proliferations, consisting of cribriform Gleason pattern 4 and solid Gleason pattern 5, with decreasing inter-epithelial lumen sizes and frequencies.…”
Section: Discussionmentioning
confidence: 99%